Optimalisasi Pemanfaatan Toga Dan Tanaman Krokot Melalui Sosialisasi di SDN 3 Serangan Untuk Meningkatkan Kepedulian Lingkungan - Surya Tapa, I Gede Fery; Liemena, Made Prema Putri (To Maega : Jurnal Pengabdian Masyarakat, 2025)
Family medicinal plants (TOGA) and purslane have many health benefits and can be utilized as part of environmental conservation efforts. Through socialization at SDN 3 Serangan, students are educated on the importance of planting and caring for these plants to increase their awareness of their benefits. This Community Service Program (PENGABDIAN MASYARAKAT) aims to optimize the use of family medicinal plants (TOGA) and purslane plants through socialization to students of SDN 3 Serangan in order to increase environmental awareness. The methods used in this activity include interactive counseling, direct demonstrations of planting TOGA and purslane, and practices of processing plants into simple products such as herbal tea and healthy food. Socialization was carried out with a participatory approach, where students not only received material but were also directly involved in the process of planting and caring for plants. The results of the activity showed an increase in students' understanding of the benefits of TOGA and purslane, which was shown through questionnaires before and after socialization. In addition, students were more enthusiastic in maintaining and developing small gardens in the school environment, and had a higher awareness of the importance of plants as a source of natural medicine and environmental preservation efforts. With this program, it is hoped that the use of TOGA and purslane plants can continue as part of healthy and environmentally friendly habits at SDN 3 Serangan.